Implementation Final Income Tax Payment Transfer Of Land And Building Based On Government Regulation No. 34 Of 2016 On Sustainable Pt.Citra Lestari Propertindo In The District Of Cirebon - Mohammad Ghozali; Umar Ma’ruf (Jurnal Akta, 2019)
The purpose of this study was to identify and analyze the implementation of the final income tax payments on acquisition of land and buildings based on Act No.34 of 2016 government regulation on Sustainable PT.Citra Lestari Propertindo in Cirebon regency, akibathukum for PPAT which have signed but not yet received evidence AJB PPH Final validation by the study used KPP Pratama. Methode is sociological juridical nature of this research using descriptive analysis, type and sources of data used are dataprimer obtained by interviews, data retrieval and datasekunder obtained from the law books, Regulations. Based on research and discussion can concluded that PPAT in running position Has Violated the signing of AJB first, in fact have not met the requirements of signing one of them has not received evidence PPH Final validation of KPP Pratama because PT.CLP having problems is the lack of complementary requirement form an attachment validation, causing delays in the issuance of evidence of validation, therefore AJB who first signed by PPAT without evidence PPH Final validation result is void due to the unlaw  of KUHPdt 1869. Law impact is the provision of sanctions which will apply to the PPAT under Article 6 paragraph (1) of the 2017 No.112 of 2017 ATR KEPMEN Code, IPPAT.Keyword: Payment PPH Final, Assignment Land and buildings, PT.Citra Lestari Propertindo.